Pengaruh Nilai Utilitarian dan Ketidakpuasan terhadap Perpindahan Merek melalui Variety Seeking sebagai Variabel Intervening (Studi pada Mahasiswa SI FISIP UNDIP yang Pernah Menggunakan Smartphone Samsung dan Berpindah ke Merek Lain) - Yani, Ahmad; Farida, Naili (Jurnal Ilmu Administrasi Bisnis, 2017)
This research based on the high growth of smartphone business development, this phenomenon is characterized with increasing number of smartphone brand that released by smartphone vendor that offer a lot of new features of its products. Samsung smartphone nowadays being a market leader in Indonesia and in the world, however in 2012-2015 samsung’s market share always decreased throughout the year while at the same time market share’s rival competitor such as Xiaomi, Oppo, Asus and etc always increased. The sole purpose of the research is to find out the effect of utilitarian value and dissatisfaction to brand switching through see variety seeking as intervening variable. The type of the research is explanatory research, with data collecting technique with questionnaire and interview. Data collecting sampel using pusposive sampling technique. Sample in this research is 100 respondents that used SAMSUNG smartphone and switched to another brand. This research use a qualitative and quantitave technique analysis. Quantitative analysis use validity test, realibility test, correlation coefficient, simple and multiple regression analysis, determination coefficient, signification test (two direction), and two steps regression.The results showed that there are positive effect utilitarian value and dissatisfaction to variety seeking, and variety seeking has a positive impact to brand switching. Based on the two steps regression analysis showed utilitarian value variable and dissatisfaction has an effect to variety seeking,. Next, variety seeking variable has an effect to brand switching.